The importance of local mucosal HIV-specific CD8(+) cytotoxic T lymphocytes for resistance to mucosal viral transmission in mice and enhancement of resistance by local administration of IL-12. - Belyakov, I M (1998)
Although crucial to mucosal vaccine development, the mechanisms of defense against mucosal viral infection are still poorly understood. Protection, cytotoxic T lymphocytes (CTL), and neutralizing antibodies have all been observed, but cause and effect have been difficult to determine. The ability of CTL in the mucosa to mediate protection against mucosal viral transmission has never been proven. Here, we use an HIV peptide immunogen and an HIV-1 gp160-expressing recombinant vaccinia viral intrarectal murine challenge system, in which neutralizing antibodies do not play a role, to demonstrate for the first time that long-lasting immune resistance to mucosal viral transmission can be accomplished by CD8(+) CTL that must be present in the mucosal site of exposure. The resistance is ablated by depleting CD8(+) cells in vivo and requires CTL in the mucosa, whereas systemic (splenic) CTL are shown to be unable to protect against mucosal challenge. Furthermore, the resistance as well as the CTL response can be increased by local mucosal delivery of IL-12 with the vaccine. These results imply that induction of local mucosal CTL may be critical for success of a vaccine against viruses transmitted through a mucosal route, such as HIV.